Chemical Composition Simplification of the Seydisehir (Konya, Turkey) Alumina Plant Waste - Kalsen, Tugba Selcen Atalay; Karadag, Hakan Burak; Eker, Yasin Ramazan; Kerti, Isil (SPRINGER, 2019)
Red mud, a residue of alumina production from bauxite refining, contains oxides of valuable metals such as Fe, Al, Ti, Si, Na, Ca, etc. The presence of these numerous metal oxides does not allow introducing the highly basic raw red mud within any industrial process, which leads to its storage over a wide land area. In order to simplify the chemical composition of this waste, the effects of weak acid leaching (citric acid) and strong acid leaching (hydrochloric acid) are studied. The treatment efficiency is discussed based on scanning electron microscope and X-ray diffraction analysis of solid product and inductively coupled plasma spectrometry analysis of acidic solutions. The effects of temperature and acid concentration on metals dissolution are estimated by rough kinetic considerations which present results comparable to those in the literature. More than 50% of Al and 50% of Ca detected by inductively coupled plasma mass spectrometry were separated via the organic acid process, while during leaching with HCl whole Ca, Fe, and more than 60% Ti and 80% of Al similarly determined were recovered. This confirms that within the red mud, metals behave differently under several forms with different reactivity toward acidic medium. Therefore, an eventual combination of both acids can be an efficient way to prepare them ready and suitable for possible industrial applications.
Keywords: Metal leaching; Citric acid; Red mud; Hydrochloric acid; RESIDUE RED MUD; BAUXITE RESIDUE; CITRIC-ACID; RARE-EARTHS; KINETICS; RECOVERY; DISSOLUTION; MECHANISM; BEHAVIOR; CHLORIDE; Science & Technology - Other Topics; Metallurgy & Metallurgical Engineering